MANAGING CUSTOMER RELATIONSHIPS THROUGH SOCIAL MEDIA IN SMALL BUSINESS OPERATIONS - Yigitaliev Ruzimatjon Nodirjon ugli (Ecominds Press, 2025)
This thesis discusses the issues of effective customer relationship management through the use of social networks in the activities of small businesses. In today's digital era, social networks - in particular, platforms such as Facebook, Instagram, Telegram - are gaining special importance as a means of establishing quick and convenient communication with customers. The work analyzes the methods of small businesses in studying the needs and offers of customers through social networks, disseminating information about services and products, as well as increasing customer loyalty. The main problems encountered in these processes and brief proposals for their elimination are also presented. The thesis aims to show ways for small businesses to effectively use social networks as a marketing and customer relationship management tool.
Keywords: Small businesses, social media, customer engagement, digital marketing, customer loyalty, CRM.